2021
DOI: 10.1590/1679-78256384
|View full text |Cite
|
Sign up to set email alerts
|

Tribological and Mechanical Properties of Epoxy Reinforced by Hybrid Nanoparticles

Abstract: In the present work, the nano-Aluminum oxide (Al 2 O 3 ), nano-Silicon Carbide (SiC), or a hybrid of them were infused into epoxy resin with an ultrasonic system with various weight percentage ratios of the nanoparticles. Small punch testing (SPT) and indirect tension testing were adopted to measure the tensile properties of the present nanocomposites. Pin-on-ring wear testing was also performed to examine wear performance of epoxy Al 2 O 3 and SiC nanocomposites. The Finite Element Analysis method is introduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…26 Alhazmi et al found that alumina nanoparticle reinforcement in the epoxy matrix had better wear resistance than silicon carbide. 27 Zhang et al concluded that adding titanium oxide/ titanium carbide to epoxy resin improved its wear resistance significantly. 28 Sabet et al also reported that the mechanical and fire-retardant properties of epoxy were enhanced with the addition of graphene oxide.…”
Section: Introductionmentioning
confidence: 99%
“…26 Alhazmi et al found that alumina nanoparticle reinforcement in the epoxy matrix had better wear resistance than silicon carbide. 27 Zhang et al concluded that adding titanium oxide/ titanium carbide to epoxy resin improved its wear resistance significantly. 28 Sabet et al also reported that the mechanical and fire-retardant properties of epoxy were enhanced with the addition of graphene oxide.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, two types of additives were selected and used in this study in different sizes and characteristics. The additives were nanoparticles (NPs) with a high modulus of elasticity and microfillers with good flexibility [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is no ideal maxillofacial silicone material, some with good characteristics and others with poor properties. Research is still being conducted to improve the properties of silicone elastomers [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…This paper also presents the various harvesting techniques and growing conditions of natural fibers. Alhazmi et al [41] worked on tribological and mechanical properties of hybrid composites based on epoxy resin. The results showed that the presence of nanofiller materials cannot affect any sort of improvement in terms of wear resistance of the composite material.…”
Section: Introductionmentioning
confidence: 99%